The Influence of Principal Academic Supervision and Teacher Professional Competence on Quality of Learning - Yuliza, Yuliza; Fitria, Happy; Eddy, Syaiful (Jurnal Pendidikan Tambusai, 2021)
The aims of the study are to determine the effect of principal academic supervision and work commitment together on the quality of learning. The location of this research was carried out in all public elementary schools in Sekayu District, Musi Banyuasin Regency. This type of research is a quantitative study with a determination design using an ex post facto research design. The sample in this study was the total of all teachers of public elementary schools in Sekayu District, Musi Banyuasin Regency, consisting of 143 teachers. Data collection techniques were questionnaires, documentation and observation. The data analysis technique used quantitative descriptive analysis techniques and multiple regressions. The results of this study state that [1] there is an effect of the principal's academic supervision on the quality of learning; [2] there is an effect of teachers professional competence on the quality of learning; [3] there is a joint effect of principal academic supervision and teacher professional competence on the quality of learning